Processo de impeachment no âmbito do Mercosul nas primeiras décadas do século XXI: golpe de estado ou instrumento democrático - Bonini, Naiéli Herrmann (2024)
During the 21st century, impeachment, which had previously been in disuse, gained popularity, especially in Latin America, due to its application in several countries in the region. Among these, the impeachment of Fernando Lugo in Paraguay in 2012 and the impeachment of Dilma Vana Rousseff in Brazil in 2016 stand out. These episodes were controversial and marked by social polarization, with some arguing that it was a coup d'état and others arguing that the use of the institute was fully valid. From this, it can be seen that the debates, both political and academic, have produced a fruitful production on the applicability of the institute, as well as different interpretations on the possibility of impeachment being considered a new form of coup. This question is valid when we remember that South America is marked by authoritarian regimes, therefore, in this context, it is essential to reflect on democracy in the region. That said, given the relevance and pertinence of the topic, both with regard to its socio-political implications and from a constitutional legal point of view. Based on the analysis of impeachments achieved in Latin America, especially in the first decades of the 21st century, the problem of this research aims to answer: can impeachment be considered an effective instrument for democratic consolidation or can it consist of a coup d'état. The general objective of this dissertation is precisely to problematize the legal institute of impeachment as a democratic instrument in Latin America, based on the analysis of impeachments that occurred on the continent from the first decades of the 21st century onwards. The line of research that the dissertation is included in is Constitutional Jurisdiction and Democracy, in the area of ​​concentration of New Paradigms of Law, of the Stricto Sensu Postgraduate Program - Master's in Law of the School of Legal Sciences of the University of Passo Fundo. The approach method used in the Master's Dissertation research was inductive and the bibliographic technique.